Managing Internal Inflammatory Root Resorption and Perforation of a Mandibular Primary Molar: A Case Report With 15 Months Follow‐Up - Mana Mowji; Motahareh Khosrojerdi (Clinical Case Reports)
ABSTRACT In the present case, calcium‐enriched mixture (CEM) cement demonstrated an excellent ability to impede internal inflammatory root resorption in a second primary molar with poor prognosis of a 5‐year‐old boy with an extremely immature apex.